Effort Increase Ability Count Beginnings Through Method Jarimatika for Children Aged 4-5 Years at RA Babuttaqwa Ward Fir Year Teachings of 2021/2022 - Zata Fakhrana Idzna; Juli Yanti Harahap (PT Inovasi Pratama Internasional, 2022)
Study this aim for increase ability counting start through method fingers that can increase ability counting start in know draft number child especially at the age of 4-5 years in RA Babuttaqwa, seen from level success son on results research that has conducted researcher in observation and documentation at the RA Babuttaqwa school . Type study this is qualitative descriptive . There is one still child not yet capable counting use finger fingers his hands because still difficult and confused for counting start use finger his hands , moment To do count the second time using fingers her , child already start capable do it in accordance with stages development and age child. Method Jarimatika could increase ability counting beginning , and in special method Jarimatika could applied in enhancement ability counting start in children 4-5 years old at RA Babuttaqwa ward Fir.